Peran Perbankan Syariah Dalam Pengimplementasian Keuangan secara Global di Indonesia - Risma Haryani Siregar; M. Irwan Padli Nasution (MES Management Journal, 2023)
The purpose of this study was to investigate how Islamic banks helped to implement financial inclusion in Indonesia.Financial inclusion is the process of making formal financial access available to those with low incomes who are unbanked.Mixed research was used in the design of this study, which combined qualitative and quantitative methods.Using Straruss and Corbin's theory, the qualitative data were analyzed in three main steps:selective coding, open coding, and axial coding.Comparative analysis of financial statements and financial ratios like CAR, ROA, ROE, NPF, and FDR were used to conduct a quantitative analysis of the data from 2010 to 2014.A significant increase in funding and financing between 2010 and 2014, as well as the findings of a financial ratio analysis, indicate that Islamic banking's performance and financial condition are excellent. This study demonstrated that Islamic banking had great potential for implementing financial inclusion. Keywords: Islamic banks; financial inclusion; financial exclusion.